Synthesis of some N-hydroxycinnamamide and N-hydroxybenzamide Derivatives Bearing Amide Bonds Targeting HDAC - Quoc, Nguyen Cuong; Quang, Le Dang; Tuan, Nguyen Duy; Y, Nguyen Thi Nhu; Men, Tran Thanh; Tuan, Nguyen Trong; Hue, Bui Thi Buu; Linh, Nguyen Vu; Huong, Lam Thi Ngoc; De, Tran Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1DO - 10.25073/2588-1140/vnunst.5406, 2023)
Recently, hydroxamic acid has attracted considerable interest because of its ability to inhibit a variety of metal-containing enzymes such as metalloproteases, lipoxygenases, histone deacetylases, and cancer cells. For example, hydroxamic acid derivatives (vorinostat, belinostat, givinostat, panobinostat) have been approved by the US FDA for the treatment of various cancers. Based on the N -hydroxycinnamamide and N -hydroxybenzamide framework, the study described and synthesized N -hydroxycinnamamide and N -hydroxybenzamide derivatives bearing amide bonds as histone deacetylases enzyme inhibitors. The structures of the compounds were determined through modern NMR spectroscopy. The compounds were then molecularly docked to the active site of the HDAC6 enzyme, the results showed that the compounds strongly bound to the zinc ion and key amino acids. These results suggest that the synthesized N -hydroxycinnamamide and N -hydroxybenzamide derivatives are potential molecular targeted therapy for HDAC positive cancer in the future.